Determining basic technological parameters for the process of electrochemical regeneration of hydrochloride-acid concentrated process solutions - Yatskov, Mykola; Korchyk, Natalia; Budenkova, Nadia; Mysina, Oksana; Kyryliuk, Svitlana (Eastern-European Journal of Enterprise Technologies, 2026)
This work investigates model chloride solutions, copper-containing chloride acid (peroxide and ammonia) spent technological solutions for etching printed circuit boards, in order to design unified technologies and equipment. This paper reports results of research on determining basic technological parameters for electrochemical regeneration that provide energetically favorable conditions for the process. It was established that when maintaining Eh in the cathode chamber from 400 mV to 450 mV, the specific current consumption for the regeneration process (38–40% copper extraction degree) is from 46 · 103 C/mol to 48 · 103 C/mol (current consumption from 15 · 103 C/l to 36 · 103 C/l), which is 4 times less compared to electrolysis without Eh correction. The study has made it possible to carry out regeneration in a diaphragm electrolyzer under energy-efficient conditions and increase the maximum degree of copper extraction from 43% to 98% by adjusting Eh. In this case, the specific current consumption is 4 times lower than that without adjusting Eh. Maintaining Eh in the cathode chamber at about 450 mV allows for more complete extraction of copper. Adjustment of the composition and redox properties of the regenerated solutions is carried out by mixing in a certain ratio of SPS with catholyte and anolyte. It is recommended to send the mixture of catholyte and anolyte after electrolysis to a centralized wastewater treatment system. Experimental and industrial studies of the basic elements in the schemes of electrochemical regeneration in a diaphragm electrolyzer given in this work have been carried out. These schemes are supplemented with additional elements for pre-treatment: an intermediate tank, a diaphragm-free electrolyzer (for adjusting Eh); and a chamber adjacent to the anode (for adjusting the composition of the solution after regeneration)